2016
DOI: 10.3389/fnhum.2016.00426
|View full text |Cite
|
Sign up to set email alerts
|

Bihemispheric Motor Cortex Transcranial Direct Current Stimulation Improves Force Steadiness in Post-Stroke Hemiparetic Patients: A Randomized Crossover Controlled Trial

Abstract: Post-stroke patients usually exhibit reduced peak muscular torque (PT) and/or force steadiness during submaximal exercise. Brain stimulation techniques have been proposed to improve neural plasticity and help to restore motor performance in post-stroke patients. The present study compared the effects of bihemispheric motor cortex transcranial direct current stimulation (tDCS) on PT and force steadiness during maximal and submaximal resistance exercise performed by post-stroke patients vs. healthy controls. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 44 publications
(63 reference statements)
2
35
2
Order By: Relevance
“…The use of cathodal stimulation had its beneficial effect diagnosed in the improvement of the motor control in people affected by stroke. 24 In this study, cathodal tDCS was used associated with muscular control of the elbow flexors in post-stroke subjects, classified as having a moderate level of impairment. The study showed that the subjects presented significant results in the increase of the control of the effort of the muscle group related to the brain region injured by the stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cathodal stimulation had its beneficial effect diagnosed in the improvement of the motor control in people affected by stroke. 24 In this study, cathodal tDCS was used associated with muscular control of the elbow flexors in post-stroke subjects, classified as having a moderate level of impairment. The study showed that the subjects presented significant results in the increase of the control of the effort of the muscle group related to the brain region injured by the stroke.…”
Section: Discussionmentioning
confidence: 99%
“…With the cathodal current, the focus is to decrease the excitability of the region opposite the lesion that may already be excited. 22,11,24 Regarding the intensity and duration of the stimulations, the studies presented three types of stimulation, with a current of 2mA for 40, 20, 15 or 10 minutes, 17,12,8,15,4 with 1mA for 20, 15 and 10 minutes 16,10,27,7 and with 1.5mA for 20 minutes. 14 Despite the discrepancies, Nitsche and Paulus 3 affirm that, after one hour of tDCS for 20 minutes at 2mA, it is possible to verify changes in cortical excitability.…”
Section: Discussionmentioning
confidence: 99%
“…In contract, among other tDCS studies, this first triple-blind study provides cogent evidence that the enhancement of knee torque was not seen with anodal tDCS combined with muscle strength training during each training session, compared to the sham tDCS with muscle strength training (Figure 4). However, the acute effects are inconsistent across studies (Tanaka et al, 2009, 2011; Montenegro et al, 2015, 2016; Angius et al, 2016; Washabaugh et al, 2016) and seem dependent on tDCS protocols, training tasks, muscle groups, and subject populations. In this context, computational modeling would be useful to understand the different spatial distributions of the electric field induced by different tDCS protocols (electrode configuration, size, or current intensity; Laakso et al, 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The application of anodal tDCS to the primary motor cortex of the lower extremity transiently increases corticospinal excitability in healthy individuals (Jeffery et al, 2007; Tatemoto et al, 2013) and improves motor function in healthy individuals and patients with stroke (Tanaka et al, 2009, 2011; Madhavan et al, 2011; Sriraman et al, 2014; Chang et al, 2015; Montenegro et al, 2015, 2016; Angius et al, 2016; Washabaugh et al, 2016). Thus, anodal tDCS has a potential to become a new adjunct therapeutic strategy for the rehabilitation of leg motor function and locomotion following a stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation